Implementation and Evaluation of a Social Media-Based Communication Strategy to Enhance Employee Engagement: Experiences From a Children's Hospital, Pakistan - Muneera A. Rasheed; Alma Arshad Hookmani; Sana Waleed; H. Sundus Fatima; Soha Siddiqui; Muhammad Khurram; Babar S. Hasan (Frontiers Media S.A., 2021)
Social media can complement organizational communication strategy which is integral to employee engagement. However, successful case studies which can allow replication are limited. The objective of the study is to describe the design, implementation, and evaluation of a social media-based communication strategy in a tertiary care hospital in Pakistan. The leadership of the pediatric service line developed an intervention plan to engage the employees with the newly reframed vision to improve patient and family experience. An online communication platform-Facebook page-was created for all employees of the pediatric service line. The strategy to influence employees was based on Cialdini's six principles of persuasion. Implementation of the strategy between October 2017 and December 2019 was evaluated for reach, discussion themes, and outcomes using the framework by Murdough (2009). Quantitative indicators included total posts, mean comments, and reactions per post. Posts were qualitatively analyzed with an emergent approach for insights into the discussion. The analysis revealed a total of 9,085 posts, with mean reactions per post of 8.4, mean comments of 7.2, and active viewership by 90% members on average. In terms of post types, photos were the highest (4,779), while videos were the lowest (1,163). Qualitative analysis indicated 54% of the posts were of the theme "inspirational and thought provoking," while the greatest engagement was generated on the theme "challenges and solution." The authors conclude that the strategy was successfully implemented to maintain active membership, engage employees in meaningful conversations, and have them express intent to execute quality improvement projects.